Extra Fructose in the Growth Medium Fuels Lipogenesis of Adipocytes - Armin Robubi; Klaus R. Huber; Walter Krugluger (Hindawi Limited, 2014)
Fructose in excessive amounts exerts negative effects on insulin sensitivity, blood pressure, and liver metabolism. These adverse outcomes were attributed to its disturbances of key metabolic pathways in the liver. Recently, possible consequences of high fructose levels directly on adipocytes in vivo have been considered. We have cultured adipocytes in growth media containing 1 g/L fructose additionally to glucose and monitored the cells fate. Cells developed lipid vesicles much earlier with fructose and showed altered kinetics of the expression of mRNAs involved in lipogenesis and hexose uptake. Adiponectin secretion, too, peaked earlier in fructose containing media than in media with glucose only. From these data it can be speculated that similar effects of fructose containing diets happen in vivo also. Apart from toxic action on liver cells, adipocytes might be stimulated to take up extra fructose and generate new lipid vesicles, further dysregulating energy homeostasis.